TURNOVER'S IMPACT ON PROFITABILITY IN THE COMERCIAL COMPANIES DEALING WITH DAIRY FARMING - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin SERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed turnover indicators in terms of working capital (WCT), total assets (TAT) and fixed assets (FAT) on the profitableness in term of return on assets (ROA) and equity (ROE) of six companies, codified F1-F6, dealing with dairy farming in the surroundings of Bucharest, the capital of Romania in the period 2009-2018. Descriptive statistics, correlation and determination coefficients, as well as polynomial regression models were used to process the data in order to prove in what measure the increase of turnover could have a beneficial effect on effectiveness of the business. Despite that the firms are in the top for their financial results, it was noticed a large variation regarding the dynamics of sales and profit, but the general trend was an increasing one. Based on the indicators taken into account, the resulting hierarchy of the companies was F5, F2, F1, F3, F4 and F6. A weak relationship was found between WCT, TAT and FAT and ROA and ROE, with a few exceptions as follows: in F4, r =0.540 between WCT and ROA, r=0.703 between TAT and ROA, r = 0.806 between FAT and ROA and r=0.565 between WCT and ROE, in F5, r=0.565between WCT and ROE, and in F6 r = 0.601 between TAT and ROA and r = 0.525 between FAT and ROA. Another conclusion was that in F4, the variation of WCT and TAT could influence the variation of ROA, and the variation of FAT could influence the variation of ROE in a higher measure. The polynomial regression models showed that in F4, one more unit of TAT could determine an increased ROA by 0.2609, and one more unit of FAT could led to a higher ROA by 0.333 and of ROE by 0.970. In F5, one more unit of WCT could grow ROE by 3.895, and one more unit TAT will determine a higher ROE by 0.282. As a final conclusion, in financial management of the dairy companies turnover must be carefully managed in order to get a higher effectiveness and profitability of the business.